Managers’ risk and time preferences in economic behavior: Review from the experiments - Kim, Huong Trang; Nguyen, Quang (Journal of International Economics and Management, 2019)
This survey reviews the recent developments in experimental studies on managers’ preferences, with a focus on issues of experimental design. We concentrate our attention on studies that measure risk and time preferences. We review a number of models of risk and time preferences that have been estimated or otherwise studied using experimental methods, and highlight some issues associated with such models. We then survey thoroughly the theoretical and empirical studies to date in this area outside and in Vietnam. We conclude by discussing some potential research avenues in the future.